Cultural Intelligence Meets EdTech: A Systematic Review on Integrating Local Wisdom into Digital Teaching to Foster Learning Engagement - Rahayu, Bening Mujianti; Muhyidin, Asep; Jamaludin, Ujang (FKIP Universitas Lampung, 2025)
Cultural Intelligence Meets EdTech: A Systematic Review on Integrating Local Wisdom into Digital Teaching to Foster Learning Engagement. Objectives: The advancement of educational technology has driven the emergence of innovative approaches that combine cultural intelligence with the use of digital technology in learning processes. This study aims to explore and map trends, types, and the impact of digital teaching materials based on local wisdom on student learning engagement. Methods: The research was conducted using a systematic literature review method with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. The inclusion criteria include: (1) articles published between 2019–2024; (2) peer-reviewed journals and indexed proceedings; (3) relevant topics; (4) scientific research articles; and (5) written in international languages such as English. Findings: The findings show an increasing trend of publications in the last decade, particularly on culturally based learning using interactive digital media. Three main types of digital teaching materials identified include audio (such as narrations of local legends), visual (such as cultural infographics), and audio-visual (such as traditional animation videos). Synthesizing the findings across studies, these culturally grounded materials significantly enhance cognitive engagement by deepening conceptual understanding, strengthening affective engagement through the reinforcement of cultural identity and emotional connection, and supporting psychomotor engagement by fostering practice-based learning tied to local traditions. Implications for practice and policy include the need to support the dissemination of culture-based digital materials, prioritize the development of immersive audio-visual media, and promote learning designs that enhance cognitive, emotional, and practical student engagement. Conclusion: The review highlights that local wisdom, when effectively embedded into digital media, serves not only as an instructional aid but also as a cultural bridge that deepens student involvement and relevance in learning. Integrating culturally responsive content in digital formats enables educators to design more authentic and impactful learning experiences. Keywords: local wisdom, digital teaching materials, learning engagement, a systematic literature review.